2019
DOI: 10.1177/1078155219872786
|View full text |Cite
|
Sign up to set email alerts
|

The impact of corticosteroid use during anti-PD1 treatment

Abstract: Background The advent of anti-PD1 therapy for cancer treatment has led to improvements in response rates and overall survival. However, anti-PD1 therapy has the potential to cause immune-related adverse events (irAEs), which can be treated with corticosteroids if severe. The clinical implications of concomitant immunotherapy and systemic steroids remain unclear, as short courses of steroids do not significantly suppress T-cell function. The primary objective of this study is to determine if the use of concomit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 22 publications
3
34
0
1
Order By: Relevance
“…CS use during these later CPI treatment periods may have different biological implications and different underlying reasons, such as management of immune-mediated adverse events. 18 , 23 Our findings are consistent with recent reports of clinical outcomes associated with CPI treatment and bCS use in many of the same tumor types, including shorter OS and/or progression-free survival (PFS) in patients who received concomitant CSs with CPI 20 22 , 27 , 30 , 38 , 39 – although some differences have emerged in smaller study populations or subgroups, such as those receiving CSs related versus unrelated to cancer care. 24 , 30 , 38 …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…CS use during these later CPI treatment periods may have different biological implications and different underlying reasons, such as management of immune-mediated adverse events. 18 , 23 Our findings are consistent with recent reports of clinical outcomes associated with CPI treatment and bCS use in many of the same tumor types, including shorter OS and/or progression-free survival (PFS) in patients who received concomitant CSs with CPI 20 22 , 27 , 30 , 38 , 39 – although some differences have emerged in smaller study populations or subgroups, such as those receiving CSs related versus unrelated to cancer care. 24 , 30 , 38 …”
Section: Discussionsupporting
confidence: 89%
“…Defining the duration of “early” CS use may also be an important factor in interpreting our findings along with those of other recent studies. Although poorer clinical outcomes were observed in patients who received CSs for >2 weeks vs ≤2 weeks, 27 studies that focused on longer time periods – such as 8 weeks 24 or 3 months 30 to define “early” CS use after starting CPI treatment – did not find significant associations. Svaton 41 did not find significant differences for a 2-month period of CS use around CPI treatment, which the authors attributed to a small number of low-dose CS users (22 out of 224 patients).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Although in the analysis by Weber et all no significant difference in ORRs was found between patients who received systemic corticosteroids due to treatment-related AEs in comparison to those who did not require/received systemic corticosteroids [15], corticosteroids are expected to affect the development of responses (if administered before response) or response duration (if administered after best response). It was primarily shown that long usage of high-dose steroids during anti-PD1 therapy is associated with shorter survival [89].…”
Section: Correlation Of Nivolumab Safety With Outcomesmentioning
confidence: 99%